2017
DOI: 10.7717/peerj.3437
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem succession of gut microbial communities in deceased human subjects

Abstract: The human microbiome has demonstrated an importance for the health and functioning in living individuals. However, the fate of the microbiome after death is less understood. In addition to a better understanding of microbe-mediated decomposition processes, postmortem succession of human-associated microbial communities has been suggested as a possible forensic tool for estimating time since death, or postmortem interval (PMI). The objective of our study was to document postmortem changes in human gut bacterial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
98
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 35 publications
6
98
1
2
Order By: Relevance
“…Postmortem microbial communities, regardless of carcass species, are regularly dominated by bacteria from phyla Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria (26)(27)(28)(29)(30)41) with other phyla such as Verrucomicrobia and Fusobacteria observed with some regularity (39,41,42). The current results complement these studies by demonstrating that bacteria from these same phyla can be cultured under aerobic and anaerobic conditions.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Postmortem microbial communities, regardless of carcass species, are regularly dominated by bacteria from phyla Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria (26)(27)(28)(29)(30)41) with other phyla such as Verrucomicrobia and Fusobacteria observed with some regularity (39,41,42). The current results complement these studies by demonstrating that bacteria from these same phyla can be cultured under aerobic and anaerobic conditions.…”
Section: Discussionsupporting
confidence: 78%
“…As observed by Chun et al (25), this habitat selected for a microbial community comprising phyla Firmicutes and Proteobacteria. These phyla are regularly associated with decomposing remains (26)(27)(28)(29)(30) and are likely reducing sulfur compounds to acquire energy (Fig. 6c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Furthermore, according to DeBruyn and Hauther (), Clostridia are organisms known for their role in advancing the process of decay; therefore, their observed rise in relative abundance may be due to an increase in available nutrients and energy obtained from fermentation reactions (DeBruyn and Hauther ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified many different taxa as being associated with manner of death, including Lactobacillus , Enterobacteriaceae, Sediminibacterium, Blautia , Rhizobiales, and Clostridium. In several recent postmortem microbiome studies, the clostridia were observed to proliferate postmortem (11, 12), potentially in part due to an increase in available nutrients and energy obtained from fermentation reactions (34). Most Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%